O sol e o sal como moduladores da diversidade de formigas na restinga ao longo do ano - Rocha, Douglas Marcelino da Silva (2023)
In tropical environments, seasonality is one of the factors that affect the distribution and diversity of insects, as a reflection of changes in conditions and resource availability throughout the year. Ants, abundant in these ecosystems, often respond to seasonal variations in environmental conditions and different resources. The Restinga is a coastal environment, which receives a high incidence of sun and saline spray, has chemically deprived and sandy soil and has different periods, with rainier summers and drier winters. The Restinga is, therefore, dynamic and presents investigative gaps regarding its ecological aspects, mainly related to the processes and patterns that modulate ant communities throughout the year. In this study we aimed to test the assumption that the abundance, richness and composition of ant species varies between seasons in the restinga, with the abundance and richness of species being greater in warmer periods. We hypothesize that (1) the abundance and richness of ant species are greater in seasons with greater amounts of available resources and that (2) differences in composition occur due to a greater contribution of specific ant species such as thermophiles in warmer seasons. . We carried out the study in the sandbank of the Itaúnas State Park, ES. We sampled five transects, establishing 10 sampling points in each, where we collected ants and sampled data on temperature, humidity and different types of resources (dry cover, total cover, plant richness, percentage of organic matter and sodium content). We carried out four sampling campaigns, one in each season of the year (May, August and November 2022 and February 2023). Our results partially corroborated our assumption, as only the richness and composition of ant species changed throughout the year, with no variation in relation to abundance. The first hypothesis was not corroborated for any of the estimated resources, and, in addition, we verified a negative relationship between ant species richness and sodium content in the soil. The IndVAL test was proven in new specifications that were developed for the division of communities between seasons, three of which refer to summer: Brachymyrmex sp.4, Forelius sp.1 and Pheidole sp.4. Our results allow us to conclude that the diversity of ants in the restinga has a seasonal variation, being shaped by environmental conditions. We confirmed that temperature is a modulator for ant assemblies, just as sound can be a toxic agent when present in large details in the environment. Furthermore, our results indicate that the presence of thermophilic ant species may be one of those responsible for the increase in richness in the warmer seasons.